Anti-corruption Strategies in Afghanistan: An Alternative Approach. Issue 1 (March 2016) - Singh, Danny
Afghanistan is one of the most corrupt countries in the world. This article provides a critical examination of Afghan anticorruption strategies based on formal anticorruption strategy, bureaucratic reform, and counter-narcotics. This article includes reference to some of the opinions of 70 semi-structured interviews conducted by the author in Kabul during May–June 2010 with anticorruption experts, rights-based organizations, civil society groups, ministries, and international and national organizations. The findings are that political interference from Afghan elites preserves corruption and deep roots of patron–client corruption—patronage networks and illicit drug trafficking interests with criminal groups for profitable gain—are difficult to combat with the existing anticorruption strategy. Hence, new approaches need to be attempted, such as, incorporating religion and ethics and empowering local leaders to combat corruption within a sixfold approach which involves (i) raising awareness, (ii) prevention, (iii) prosecution and sanctions, (iv) detection, (v) a collaborative counter-narcotics strategy, and (vi) linking religion.